Hepatoprotector Effect of Corn Silk Ethanol Extract (Stigma maydis) on Paracetamol-Induced White Male Rats - Nessa, Nessa; Ifmaily, Ifmaily; Putri, Yeliza; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Objectives: Corn silk (Stigma maydis) is one part of the corn plant that contains useful chemical compounds, including flavonoid compounds. The ability of flavonoid compounds to capture free radicals that cause liver damage. The purpose of this study was to determine the hepatoprotective effect of corn silk ethanol extract on male white rats induced by paracetamol and to determine the effect of varying doses of corn silk ethanol extract as a hepatoprotector. Data Sources Study Selection: This study is an experimental study testing the hepatoprotective effect of corn silk ethanol extract using male white rats Summary of contents of the article:This study using 20 male white rats which were divided into 5 groups, namely negative control given NaCMC, positive control induced by toxic dose of paracetamol, and group of corn silk ethanol extract doses of 250, 500, 1000 mg/kgBW. The measurement parameters were the levels of SGOT and SGPT enzymes, the ratio of liver weight, and histopathological examination of the liver. The data obtained were analyzed descriptively, statistically with two-way and one-way ANOVA followed by Duncan's test and. The results showed that administration of corn silk ethanol extract could reduce levels of SGOT and SGPT enzymes, and analysis using two-way ANOVA showed that there was a significant difference in levels of SGOT and SGPT in the test group with (p<0.05). The ratio of liver weight was analyzed by one-way ANOVA. The results showed that there was no significant difference to the ratio of organ weight in the test group with (p>0.05). Histopathological picture showed improvement of liver parenchymal morphology on administration of corn silk ethanol extract. Conclusion: Based on the results of the study, it was concluded that the presence of a hepatoprotector effect on the ethanol extract of corn silk and that there was an influence of the dose variation on the hepatoprotector effect with a dose of 1000 mg/kgBW was more effective as a hepatoprotector.